Hyper-personalization in digital da'wah: A critical constructivist analysis of NU Online's YouTube channel - Sitti Ansoriah Titi; Warto (Islamic Communication Journal, 2026)
This study examines audiovisual representations, linguistic styles, and audience interactions that shape hyper-personalization in digital preaching on the NU Online YouTube channel. This study confirms that digital preaching not only disseminates religious messages but also creates symbolic closeness, authority, and emotional intimacy through mediated communication, using the critical constructivism framework. Narrative transcription, visual coding, and audience comment analysis were used to analyse the qualitative content of ten videos uploaded from January to September 2025. Three main components that shape hyper-personalization are revealed by the research results: (1) visual strategies such as stable lighting, close framing, and minimalist backgrounds that enhance the image of da’i as a calm and composed figure; (2) conversational language style that uses personal pronouns to make the message feel individually addressed; and (3) audience emotional responses that form parasocial relationships. NU Online's research results not only disseminate religious knowledge but also establish religious authority through algorithms and emotional appeal. Therefore, to avoid excessive emotional dependence and maintain the authenticity of da'wah in the digital world, one must adhere to ethical standards. This study contributes to the practice of Islamic communication in digital spaces by integrating media logic with Islamic ethical principles. ***** Penelitian ini mengkaji representasi audiovisual, gaya linguistik, dan interaksi audiens yang membentuk hiperpersonalisasi dalam dakwah digital di kanal YouTube NU Online. Penelitian ini menegaskan bahwa dakwah digital tidak hanya menyebarkan pesan keagamaan, tetapi juga menciptakan kedekatan simbolik, otoritas, dan keintiman emosional melalui komunikasi yang dimediasi, menggunakan kerangka Critical Constructivism. Transkripsi naratif, pengodean visual, dan analisis komentar audiens digunakan untuk menganalisis isi kualitatif dari sepuluh video yang diunggah dari Januari hingga September 2025. Tiga komponen utama yang membentuk hiperpersonalisasi ditunjukkan oleh hasil penelitian: (1) strategi visual seperti pencahayaan stabil, framing dekat, dan latar minimalis yang meningkatkan citra da’i sebagai figur yang tenang; (2) gaya bahasa percakapan yang menggunakan pronomina pribadi yang membuat pesan terasa ditujukan secara individual; dan (3) respons emosional audiens yang membentuk hubungan parasosial. Hasil penelitian menunjukkan bahwa NU Online tidak hanya menyebarkan pengetahuan agama tetapi juga membentuk otoritas keagamaan melalui algoritma dan sentuhan emosional. Dengan demikian, untuk menghindari ketergantungan emosional yang berlebihan dan menjaga keaslian dakwah, komunikasi Islam di dunia digital harus tetap berpegang pada etika. Studi ini berkontribusi pada praktik komunikasi Islam di ruang digital dengan mengintegrasikan logika media dan prinsip-prinsip etika Islam.